AN ANALYSIS OF NINE GRADE STUDENTS' ABILITY IN WRITING PROCEDURE TEXT AT JUNIOR HIGH SCHOOL - Aulan Nisa; Nurhayati Nurhayati; Emiliya Sukma Dara Damanik (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2022)
This study discusses students' skills in writing procedural texts, using topics related to use in everyday life. This study aims to determine the level of students' ability in writing procedural texts according to the layout and linguistic elements of the text. This study used a sample of all students of class IX junior high school. The research was obtained by analyzing the students' written procedure text using an assessment rubric, namely an assessment of the general structure and linguistic characteristics of the text. Based on this research, students' ability in writing procedural texts is at a good level. Even so, there are some parts of the text such as ingredients in generic structure and adverb on linguistic elements that students do not understand how to write and need further understanding. Students are required to be able to write good procedural texts in accordance with the general structural and linguistic elements of the text.